Cost-of-illness analysis of long-term healthcare resource utilization and disease burden in patients with pulmonary embolism: insights from the PREFER in VTE registry. (3rd October 2022) - Farmakis, I; Barco, S; Mavromanoli, A C; Mahan, C E; Giannakoulas, G; Cohen, A T; Konstantinides, S; Valerio, L
Abstract: Background: Pulmonary embolism (PE) is responsible for considerable personal and societal costs. Detailing this burden would support an efficient public health resource allocation. However, cost estimates so far have failed to account for both resource utilization and excess costs in its long-term management beyond the acute phase. Purpose: To provide estimates for the economic and disease burden of PE in the European Union (EU) also accounting for long-term healthcare utilization and costs beyond the acute phase. Methods: This is a cost-of-illness analysis, from a societal perspective, with a bottom-top approach and a time horizon of 12 months based on data from the PREFER in VTE registry. We calculated direct and indirect costs of an acute PE event and its 12-month follow-up. We used cost inputs derived from the literature and as directly reported in the PREFER in VTE registry and we adjusted them for inflation and purchasing power parity to 2020 Euros (€). Total average costs per PE patient comprised six general categories: costs for the index PE hospitalization; costs for clinical events during follow-up; costs for anticoagulation after the index event; costs for ambulatory visits during follow-up; the patient's own contribution; and costs related to productivity loss (using the friction cost method). A stratified analysis was performed according to the presence of active cancer, non-cancer provoked PE, and unprovoked PE. In addition, we used the EQ-5D health questionnaire to derive a disability weight for the post-PE state 12 months after the index event and the corresponding disability adjusted life years (DALYs) presumably due to PE. Results: Annual disease-specific costs for each incident PE case ranged between 9, 135 € and 10, 620 €. Costs for patients with cancer (8, 274 to 9, 752 €) and patients with unprovoked PE (8, 695 to 9, 612 €) were lower than costs for non-cancer patients with provoked PE (10, 423 to 11, 307 €), mainly due to differences in productivity loss. The indirect costs were mainly driven by productivity losses and their proportion to total costs was 42–49% for the overall population (28–33% for cancer, 52–56% for non-cancer provoked PE and 43–47% for unprovoked PE) (Figure 1). Anticoagulation accounted for 18–21% of total costs for cancer patients (while only 5–6% for non-cancer patients) and was primarily driven by the use of low-molecular-weight heparins and fondaparinux (Figure 2). The calculated disability weight for cancer-free survivors of PE 12 months after the index event was 0.017 (bootstrapped 95% CI 0.0002–0.0344) and the estimated annual DALYs per incident case were 1.17 (bootstrapped 95% CI 0.75–1.59). Conclusion: PE imposes a significant annual economic burden, for which productivity loss is the main driver. Total costs in the EU could range between 0.5 and 3.8 billion €. The disease burden from PE is notable and translates to the loss of roughly 1.2 years of healthy life per incident PE case per year. Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): This study was supported by an unrestricted grant from Daiichi Sankyo (Title: "Filling the gaps of knowledge on healthcare outcomes during long-term anticoagulant treatment of pulmonary embolism", grant number DSE-DE-CV-20001).